Vanadia-modified Sb-CeO2/TiO2 catalyst for effective removal of NO by NH3 - Lee, Kyung Ju; Maqbool, Muhammad Salman; Pullur, Anil Kumar; Jeong, Young Eun; Song, Kwang Ho; Ha, Heon Phil (SPRINGER, 2015)
The Sb-CeO2/TiO2 (SCT) catalytic system with different vanadia loading (0-3 % w/w) was systematically investigated for removal of NO by NH3. A series of catalysts prepared by impregnation and deposition precipitation methods were thoroughly characterized physically, by BET surface area, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), and chemically, by temperature-programmed desorption (NH3 and SO2-TPD), temperature programmed reduction (H-2-TPR), and in-situ DRIFT study. NH3-TPD and H-2-TPR results for 2 and 3 % vanadia-loaded Sb-CeO2/TiO2 catalysts revealed high total acidity and reducibility. As a result, both catalysts had high activity at low temperatures. At 240 A degrees C for 20 h the 2 % vanadia-loaded Sb-CeO2/TiO2 catalyst was more resistant to SO2 than the 3 % vanadia catalyst. In addition, in-situ SO2 DRIFT study revealed the existence of more surface sulfate species on Sb-CeO2/TiO2 than on vanadia-loaded Sb-CeO2/TiO2 catalysts.
Keywords: REDUCTION; OXIDE; SO2; ADSORPTION; AMMONIA; CERIUM; METAL